Acquired hernias of the diaphragm. Issue 750 (April 1988) - Johnson, C. D.; Ellis, H.
Abstract : We present our experience over five and a half years of acquired hernias of the diaphragm. Each case represents a different presentation of this condition, which may follow blunt or penetrating trauma or iatrogenic injury. Diaphragmatic hernia may present in the acute phase after injury but late presentation may occur after many years, with chronic abdominal or respiratory symptoms, or with acute intestinal obstruction. The problems in diagnosis and management are discussed.